The Influence of Perch Height Selection on Vocalisation of Pied Triller, Lalage nigra (Aves: Campephagidae) in Suburban Landscapes, Sarawak - Amera Natasha Mah, Muhammad Adam Mah; Mohamad Fizl Sidq, Ramji (UNIMAS Publisher, 2020)
Understanding how birds utilised songs and calls to communicate among conspecifics is crucial for their survival, yet it remains an understudied area in bird ecology. We studied the influence of perch height selection on the vocalisation of Pied Triller, a common garden bird, in two suburban landscapes namely Pustaka Negeri Sarawak Recreational Park, Kuching and University Malaysia Sarawak campus, Kota Samarahan from October 2018 to February 2019. Using a Marantz recorder connected to a parabolic reflector, we recorded calls and songs during morning (0630-1030 hr) and late afternoon (1600-1830 hr). Perch object, tree species, roost substrate and perch height from the ground were identified and measured. Clear and good quality spectrograms were used directly to describe song and call types. Photos and video recordings were analysed to describe perch behaviour. The vocal output representatives were then matched to the corresponding behaviour displayed. Our results revealed that Pied Trillers emit four different vocal outputs namely (i) song type, (ii) call type A, (iii) call type B and (iv) call type C. A total of nine behaviours were observed, of which the perch-hop action was observed the most from both male and female Pied Trillers (33.71%), followed by perching (29.21%), foraging (20.22%), preening (7.78%), defecating (2.25%), eating (2.25%), roosting (2.25%), bill wipe (1.12%) and flight (1.12%). They prefer to roost on high perch to emit calls compared to songs. This probably suggest that Pied Triller prioritised vocal transmission and signalling to avoid being masked by surrounding anthropogenic noises and to avoid being conspicuous to potential predators. The most frequently visited perch object was the Weeping fig tree, Ficus benjamina.